Implementasi Enam Fungsi Subak di Perkotaan (Kasus Subak Padanggalak di Kecamatan Denpasar Timur, Kota Denpasar) - MAHMUDAH, SILFIA MARETA; WINDIA, I WAYAN; SUDARTA, WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Implementation of the Six Functions of Subak in the Urban Areas (The Case of Subak Padanggalak in East Denpasar District, City of Denpasar) With the rapid development of time, the existence of Subak is increasingly threatened due to the transfer of wetland function in urban areas where there are developments outside the agricultural sector. This research was conducted at Padanggalak Subak, East Denpasar District, City of Denpasar. The aim of this study was to determine the implementation of the six functions of Subak seen from (1) the activities of religious ceremonies, (2) the search and distribution of irrigation water, (3) the operation and maintenance of irrigation networks, (4) resources mobilization, (5) the handling of conflicts, and (6) adoption of innovations. This research used descriptive qualitative data. The results showed that the implementation of the six functions of Subak in Padanggalak had been duly made. The implementation was conducted in the religious ceremony activities performed consistently, sharing and distribution of irrigation water which was conducted in a fair way, operation and maintenance of irrigation networks, and the mobilization of resources done by means of mutual cooperation and assistance from the government, conflict handling was done amicably, and the adoption of innovations had been applied in Subak Padanggalak. It is suggested the implementation of the six functions of Subak should be maintained and even optimized to achieve a more optimal goal.
Keywords: implementation; subak functions; urban areas; subak existence